Guidance note: Carrying out a country-level stocktake - Standing Panel on Impact Assessment (2023)
This guidance note is intended for use by teams preparing an Expression of Interest (EoI) in response to SPIA’s December 2023 open call on country-level studies. The goal is to explain what we mean by a stocktake of CGIAR innovations – one of the core deliverables of each SPIA country-level study – and provide some insight into the methods and level of effort required to produce one. More detailed methodological guidance will be made available in mid-2024 to support those teams invited to develop full proposals.